The Factors That Influence Foreign Holdings of Malaysian Government Bonds - Zaidey Evon; Lee, Hock Ann (Human Resource Management Academic Research Society (HRMARS), 2021)
While the flows of global capital can facilitate optimal global monetary allocation, they can also cause global macroeconomic imbalances before and after financial crises. From this point of view, looking into what causes the flows of capital is important to prevent economic turmoil and financial crises. Therefore, this research aims to examine the impact of pull factors (domestic factors) and push factors (US unconventional monetary policy) on the foreign bondholding in Malaysia. This research analyses monthly data for the period January 2008 - April 2018 using the Autoregressive Distributed Lag (ARDL) method. The empirical results reveal that the empirical model with US total assets is the best model in investigating the impact of all the independent variables toward the foreign bondholding in Malaysia. According to the findings of this research, each of the pull variables has a significant long-run relationship with foreign bondholding in Malaysia. Most crucially, total asset, an unconventional monetary policy tool used by the United States, has a significant positive link with foreign bondholding in Malaysia. Despite these promising findings, further research should be conducted to investigate the disaggregated analysis of US total assets on the foreign bondholding of Malaysian government bonds.